Temperature-dependent surface density of alkylthiol monolayers on gold nanocrystals. (2nd March 2018) - Liu, Xuepeng; Lu, Pin; Zhai, Hua; Wu, Yucheng
Abstract: Atomistic molecular dynamics (MD) simulations are performed to study the surface density of passivating monolayers of alkylthiol chains on gold nanocrystals at temperatures ranging from 1 to 800 K. The results show that the surface density of alkylthiol monolayer reaches a maximum value at near room temperature (200–300 K), while significantly decreases with increasing temperature in the higher temperature region ( > 300 K ), and slightly decreases with decreasing temperature at low temperature ( < 200 K ). We find that the temperature dependence of surface ligand density in the higher temperature region is attributed to the substantial ligand desorption induced by the thermal fluctuation, while that at low temperature results from the reduction in entropy caused by the change in the ordering of passivating monolayer. These results are expected helpful to understand the temperature-dependent surface coverage of gold nanocrystals.